Staff Studies for the World Economic Outlook, December 1993. (World Economic and Financial Surveys; World Economic and Financial Surveys ;, 1994)
This paper focuses on the private nonfinancial sectors of the affected economies, financial liberalization provided households and businesses with greater access to credit markets. This contributed to the long period of expansion during the 1980s. Partly as a result of major changes to the financial systems, several industrial countries had a boom in asset markets associated with a period of asset accumulation, an unprecedented buildup of debt, a sharp increase in relative asset prices, and related increases in household wealth. The expansion in household financial activity in the United Kingdom during the 1980s was paralleled by a sizable boom in investment spending and an increase in corporate debt. The structure of balance sheets was also affected by mergers and acquisitions that led to a further expansion in corporate debt. New types of bank loans and accounts have prevented even greater disintermediation but have also reduced net interest margins because more deposits now earn market-related rates of return.